The Influence of Interpersonal Communication, Professionalism and Competence on The Monitoring System and Hospital Paramedic Performance at Dr. H. Soewondo Kendal Regional Hospital - Anindita Paramastuti Azuma; Hindyah Ike Suhariati; Raden Roro Ratuningrum Anggorodiputro; Delladari Mayefis; Nelwetis (CV. Get Press Indonesia, 2025)
The performance of paramedics, especially nurses and midwives, is essential to the quality of hospital health services. This study aims to examine the influence of interpersonal communication, professionalism, and competence on the monitoring system and nurse performance at at Dr. H. Soewondo Kendal Regional Hospital. Using a quantitative approach with SEM-PLS and WarpPLS 5.0, data from 110 paramedics (92 nurses and 18 midwives) were analyzed. The results show that interpersonal communication, professionalism, and competence significantly influence the monitoring system (R² = 0.79), which in turn positively affects nurse performance (R² = 0.73). However, competence does not have a significant direct effect on performance without the mediation of the monitoring system. These findings suggest that improving internal factors along with an effective monitoring system can enhance overall paramedic performance and support hospital management in optimizing human resources.